Evangeline as Identity Myth - Le Blanc, Barbara (Ethnologies)

(untitled) (Association Canadienne d’Ethnologie et de Folklore, 1993)
This article examines Evangeline as an identity myth, which during the late nineteenth and early twentieth centuries, contributed in promoting a feeling of unity among members of the Acadian people. After a brief examination of the four stages of myth — spring, summer, autumn and winter — the reader is plunged into the four levels of myth — geographical, economical, sociological and cosmological. The study of the four levels shows how the use of reality in the myth’s description acts as a bridgehead between present and past. Finally the exploration of the changes in vitality of the Evangeline myth begins with the primary phase or creation of the story. It then looks at the implicit phase or acceptance of the tale by a wide audience. Lastly, it considers the present rationalized questioning phase. Examination of these three phases of vitality allow the reader to comprehend how perceptions and the use of Evangeline have changed since her first creation up until the present day. The conclusion suggests that if myth is a way of finding meaningful existence, as well as emotion translated into image in order to promote a sense of group identity, then Evangeline appears to fulfill this function.